2014
DOI: 10.3103/s1068366614030118
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of face mill wear effect to flat surface roughness

Abstract: In this article, we researched the effect of wear face mills to finish the surface roughness by various conditions of cutting a steel 45 workpiece. The article shows how to affect the feed, cutting speed, and tool wear of a T5K10 carbide tool on the roughness of flat surfaces. The paper analyzes the nature the microprofile of changes in machined surfaces based on increasing the wear surface on the tooth flank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Considering the same machining operation but for Inconel 718 superalloy, Tian et al [19] conducted research to evaluate the influence of machining speed on cutting forces, as well as on tool wear. The study of Pimenov [20] revealed the influence of face mill wear on the surface roughness parameter when the subject material was steel-45. Cui and Zhao [21] studied the machinability of AISI H13 steel, hardened and machined as face milling.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the same machining operation but for Inconel 718 superalloy, Tian et al [19] conducted research to evaluate the influence of machining speed on cutting forces, as well as on tool wear. The study of Pimenov [20] revealed the influence of face mill wear on the surface roughness parameter when the subject material was steel-45. Cui and Zhao [21] studied the machinability of AISI H13 steel, hardened and machined as face milling.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main precision criteria in face milling is sur-face roughness, Ra. Surface roughness has in various papers (Fernández-Valdivielso et al 2016;Pimenov 2013aPimenov , 2014 been shown to increase with increased flank wear of face mill teeth. Workpiece specifications will usually detail the maximum roughness value that has to be machined.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients of determination values are comparable to that of and, hence, the same conclusions are valid. Equation (2) represents the relationship between and studied factors: The values for optimum (minimum) are as follows: = 500 rpm, = 0.29 mm, and = 50 mm/min. It is noticed that only the feed rate value is common between minimum and minimum .…”
Section: 2mentioning
confidence: 99%
“…Pimenov [2] investigated the effect of feed, cutting speed, and tool wear of a T5K10 carbide tool on the roughness of flat surfaces, produced by face milling, of steel 45. The 2 Advances in Materials Science and Engineering work analyzed the nature of the microprofile of changes in machined surfaces based on increasing the wear surface on the tooth flank.…”
Section: Introductionmentioning
confidence: 99%